Cellular immune response to SARS-CoV-2 in patients with primary antibody deficiencies - Mizera, Dorota; Dziedzic, Radosław; Drynda, Anna; Gradzikiewicz, Ada; Jakieła, Bogdan; Celińska-Löwenhoff, Magdalena; Padjas, Agnieszka; Matyja-Bednarczyk, Aleksandra; Zaręba, Lech; Bazan-Socha, Stanisława (Frontiers in Immunology, 2023)
Introduction: Primary antibody deficiencies (PAD) are inborn defects of the immune system that result in increased susceptibility to infections. Despite the reduced response to vaccination, PAD patients still benefit from it by reducing the risk of severe infections and complications. SARS-CoV-2 vaccines are recommended in PAD patients, but their immune effects are poorly studied. Here, we analyze virusspecific T-cell responses in PAD patients after booster vaccination against SARS-CoV-2.Patients and methods: The study included 57 adult PAD patients on long-term immunoglobulin replacement therapy (IgRT) diagnosed with X-linked agammaglobulinemia (XLA; n = 4), common variable immunodeficiency (CVID; n = 33), isotype defects or IgG subclass deficiency (n = 6), and unclassified IgG deficiency (n = 14). Of those, 49 patients (86%) received vaccination against SARS-CoV-2 using mRNA vaccine (Pfizer-BioNTech). T-cell responses were assessed at a median of 21 (13 -30) weeks after the booster dose (mainly the third dose) using commercially available interferongamma release assay (IGRA) with recombinant SARS-CoV-2 spike S1 protein.Results: Vaccinated PAD patients showed an increased (3.8-fold, p = 0.004) release of IFN-γ upon S1 stimulation. In this group, we also documented higher serum levels of anti-SARS-CoV-2 IgG (4.1fold, p = 0.01), although they were not associated with IGRA results. Further subgroup analysis revealed very similar IGRA responses in CVID and unclassified IgG deficiencies that were 2.4-fold increased compared to XLA and 5.4-fold increased compared to patients with isotype defects or IgG subclass deficiencies (e.g., vs. CVID: p = 0.016). As expected, CVID and XLA patients showed decreased serum titers of anti-SARS-CoV-2 antibodies compared to other studied groups (e.g., CVID vs. unclassified IgG deficiency: 4.4-fold, p = 0.006). The results did not depend directly on IgRT mode or dose, number of vaccine doses and time from the last booster dose, and clinical manifestations of PAD. Interestingly, anti-SARS-CoV-2 titers were positively correlated with serum immunoglobulin levels before IgRT (e.g., for IgA: r = 0.45, p<0.001; for IgG: r = 0.34, p = 0.009) and the percentage of peripheral blood NK cells (r = 0.48, p<0.001).Conclusions: Our results documented satisfactory in vitro cellular immune response in PAD patients after booster SARS-CoV-2 vaccination.